(3CKQ GJaGbjGJ GdLGJ Ydi GdfXGe GdOSJhQj GdeUQj (B: s (3OQGSI ebGQfI (B/ s - (3YRJ eMeO SYO GdRYhjdjs; (3LGHQ LGO fUGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3JYO GJaGbjGJ GdLGJ hefXeI GdJLGQI GdYGdejI cCMO hLhg GdYhdeI GdGbJUGOjI hGdbGfhfjI PGJ JGKjQ Ydi GdSdWGJ GdKdGK ddOhd aGdSdWI GdJTQjYjI JUHM edReg HJhajb bhGfjfgG GdOGNdjI eY GdJRGeGJgG GdOhdjI YfO JYGQVgG hjJWdH gPG GdJMOi ehGLgI JTQjYjI HJVGaQ GdLghO GdhWfjI HGdOQLI GdGhdi dJgjFI GdefGN GdSjGSi hGdbGfhfi hGdGbJUGOi dehGcHI gPg GdJZjQGJ GdYGdejI hHOC Mb GdOhdI GdWdjb ai JTQjYGJgG hbhGfjfgG jUWOGe HGdYOjO ef GdbjhO hGdGYJHGQGJ GdJi CUHMJ JMce Mb GdOhdI hSdWJgG ai gPG GdfWGb hjbh Vef LhGfH SjGOJgG GdJTQjYjIs
2017. (3CWQhMI (B((3OcJhQGg(B)-s
(3HHdjhLQGajG(B: (3UaMGJ (B265-290.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GJaGbjI GdLGJs; (3efXeI GdJLGQI GdYGdejIs; (3GdYhdeIs; (3GdeYGgOGJ GdOhdjIs; (3WHjYI GdSdWI GdJfajPjIs; (3GdQbGHI GdbVGFjI Ydi GdGJaGbjGJ GdOhdjIs; (3GJaGbjI GdLGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2017